Studi dan Implementasi Gelombang Elektromagnetik dalam Berbagai Aplikasi - Muhamad Aldi Firdaus; Anggie Maulia; Syuja Rifka Khairyansyah; Gilang Nur Rosyid; Diyajeng Luluk Karlina (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This study aims to examine the applications of electromagnetic waves across fields such as daily life, military, and medicine. The research highlights the importance of electromagnetic waves in modern technology. A literature review method was employed to gather data from scientific journals focusing on the history, definitions, classifications, and applications of electromagnetic waves. The theoretical framework includes the development of electromagnetic wave theory, spectrum classification, and related technologies. Results reveal the use of microwaves in ovens and satellite communication, infrared in thermal imaging and guided missiles, and X-rays and gamma rays in medical diagnostics and treatment. This study underscores the significant contribution of electromagnetic waves in enhancing technological efficiency across various sectors. The findings are expected to encourage the development of innovative applications in the future.